Caracterização fenotípica e genotípica de Listeria monocytogenes presente no processamento da carne de frango - Carvalho, Fernanda Tavares (2018)
Poultry industry in Brazil has been growing in recent years and the country has been considered the largest exporter in the world, the largest producer of chicken meat. The consumption of this protein source has also increased significantly by the food change of the population in search of healthy habits and as a result of this growth, both national and international market, has become more demanding in relation to the microbiological quality of food products. Chicken meat may, however, serve as a vehicle for a number of pathogenic microorganisms, including Listeria monocytogenes, which causes listeriosis, a serious disease with a high mortality rate that can develop meningitis, septicemia in newborns, the elderly and immunocompromised, as well as abortion in pregnant women. The objective of this study was the phenotypic and genotypic characterization of strains of L. monocytogenes previously isolated in the chicken meat processing, for which antimicrobial susceptibility analyzes, determination of the Minimum Inhibitory Concentration (MIC) of commercial sanitizing agents, molecular serotyping and genotyping by Pulsed Field Gel Electrophoresis (PFGE). In addition, a real-time PCR technique (q-PCR) was evaluated using the hly gene and used in the enrichment broth used in the search for L. monocytogenes. Thirty-seven (37) strains of L. monocytogenes were studied, of which six (6) showed negative beta-hemolysis, although they had the hly gene responsible for the expression of Listeriolysin O, the protein responsible for blood hemolysis. All strains were identified as belonging to serotypes 1/2a and 1/2c and PFGE revealed 5 different clusters, with a genetic similarity between strains of ≥ 69%, 73% of strains were resistant multidrug resistant at least 3 antibiotics of different pharmacological classes and 100% sensitive to the sanitizing agents evaluated (peracetic acid, benzalkonium chloride, chlorhexidine, sodium hypochlorite, quaternary ammonium). The q-PCR identified 20% of the isolates, while the bacteriological method identified 14%, having a sensitivity of 64%, specificity of 88%, accuracy of 89% and value of p, being 0.26, when compared to the standard method. High values indicate that this method has the potential to be used as an alternative to the standard method, such as screening, as it improves the misidentification, guarantees the quality of poultry meat and provides rapid detection of L. monocytogenes in food products, mainly by these strains showed serotypes common to cases of human listeriosis outbreaks and high antimicrobial resistance, which represents a potential threat to public health.